The Existence Of Traditional Islamic Boarding School Education In The Era Of Industrial Revolution 4.0: EKSISTENSI PENDIDIKAN PONDOK PESANTREN TRADISIONAL DALAM ERA REVOLUSI INDUSTRI 4.0 - Rizal, M.Saprawi (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
In the Era of Industrial Revolution 4.0, Islamic boarding schools are required to make changes, including changes inform, format, orientation and educational methods without changing the characteristics of the Islamic boarding school.Because the existence of Islamic boarding schools in responding to developments over time must remain committed toproviding an educational model that is capable of producing quality human resources. Moreover, the sustainability ofIslamic boarding schools lies in its traditionalism aspect, then making substantial changes to the learning system andinstitutions to adapt to the needs of the times. continues to grow. This research aims to determine the existence oftraditional Islamic boarding school education in the Industrial Revolution Era 4.0 at Al-Khairat Darussalam IslamicBoarding School, Pontianak. This research uses a descriptive method with a qualitative approach. The results of thisresearch are first, adaptation to change or responsiveness to changing times, secondly, curriculum modifications that areadapted to the needs and developments of the times. Third, build networking with the community outside the Islamicboarding school, networking with Islamic boarding school partners with the business world, networking with thegovernment and networking with civil society organizations. Fourth, developing soft skills and hard skills for students.Keywords: Islamic boarding school, Traditional ,Industrial Revolution 4.0